2010
DOI: 10.1016/j.socscimed.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Green space as a buffer between stressful life events and health

Abstract: This study investigates whether the presence of green space can attenuate negative health impacts of stressful life events. Individual-level data on health and socio-demographic characteristics were drawn from a representative two-stage sample of 4529 Dutch respondents to the second Dutch National Survey of General Practice (DNSGP-2), conducted in 2000-2002. Health measures included: (1) the number of health complaints in the last 14 days; (2) perceived mental health (measured by the GHQ-12); and (3) a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
493
5
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 906 publications
(541 citation statements)
references
References 38 publications
26
493
5
17
Order By: Relevance
“…This is validated by respondents stating that their spiritual experience would not be enhanced if the garden was larger, had a greater variety of plants, or contained certain tree species or amenities. This is contradictory to other studies illustrating that benefits received from urban green spaces increased with increasing area [11,62]. This maybe a consequence of most of the gardens in our sample being quite small (the largest being 0.5 ha).…”
Section: Discussioncontrasting
confidence: 99%
“…This is validated by respondents stating that their spiritual experience would not be enhanced if the garden was larger, had a greater variety of plants, or contained certain tree species or amenities. This is contradictory to other studies illustrating that benefits received from urban green spaces increased with increasing area [11,62]. This maybe a consequence of most of the gardens in our sample being quite small (the largest being 0.5 ha).…”
Section: Discussioncontrasting
confidence: 99%
“…While access to green spaces can foster physical activities and social contacts that are health beneficial, such mechanisms are most likely related to access to large green spaces such as parks (Dadvand et al, 2012a). Our NDVI metrics rather reflect a less polluted, more quiet and generally more appeasing residential environment (van den Berg et al, 2010). The use of 30 m resolution raster data to calculate the average NDVI within small buffers might have led to imprecise exposure estimate in case of irregular greenness patterns due to fragmented land uses, especially for the 50 m buffers.…”
Section: Discussionmentioning
confidence: 99%
“…Greenness exposure has been associated with reductions in risks of various health outcomes, including self-perceived health (Maas et al, 2006;Mitchell and Popham, 2007), blood pressure (Agyemang et al, 2007) and mortality (Villeneuve et al, 2012). The causal nature of these associations is not established to date (Bowler et al, 2010;Lee and Maheswaran, 2011) and the biological mechanisms potentially in play are not clear, but possible pathways include reduction of exposure to noise, air pollution (Dadvand et al, 2012b) and urban heat (Jenerette et al, 2011), as well as stress relief (Fan et al, 2011;van den Berg et al, 2010). Such an array of modifications might also be beneficial to pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…64,66,78 However, one quasi-experimental study of a vacant-lot greening program in Philadelphia, PA, found an association between greened vacant lots and increased physical activity. 79 Green exposure has also been shown to prevent and mitigate stress, anxiety, and depression, [80][81][82][83] especially in urban environments. 81,84,85 Access to green views has been associated with improved mental health in general 86 and more specifically has been shown to reduce mental fatigue and improve coping with stressful settings.…”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 99%